2017
DOI: 10.1177/2156759x18773277
|View full text |Cite
|
Sign up to set email alerts
|

School Counselors as Curricular Leaders

Abstract: The authors examined school counselors design of classroom curriculum lessons through a content analysis of lesson plans located on the American School Counselor Association (ASCA) Scene website. The analysis coded 139 lesson plans based on 12 lesson plan component categories and types of instructional strategies used. Findings address the frequency of topics related to the three ASCA domains, grade levels, and scores on 12 lesson components including overall total score. The article includes implications for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
24
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 26 publications
0
24
1
Order By: Relevance
“…These finding were inconsistent with literature that stated that reading proficiency improved when students of color participated in counseling programs (Bell, 2010). The findings of this study were also inconsistent with the findings of Lopez and Mason (2018) which found that participation in counseling had a positive impact on student achievement. The results from this study also revealed that mentoring was the only significant predictor of reading scores.…”
Section: Discussioncontrasting
confidence: 99%
“…These finding were inconsistent with literature that stated that reading proficiency improved when students of color participated in counseling programs (Bell, 2010). The findings of this study were also inconsistent with the findings of Lopez and Mason (2018) which found that participation in counseling had a positive impact on student achievement. The results from this study also revealed that mentoring was the only significant predictor of reading scores.…”
Section: Discussioncontrasting
confidence: 99%
“…In comprehensive school counseling programs, school counselors use a range of approaches to support students' academic achievement, social and emotional growth, and career development (American School Counselor Association [ASCA], 2012). Classroom guidance is one delivery method of such supportive approaches, advantageous in part because it allows school counselors to reach all students in their schools (ASCA, 2012;Lopez & Mason, 2018). This curriculum is ideally "a planned, written instructional program that is comprehensive in scope, preventative in nature, and developmental in design" (ASCA, 2012, p. 85).…”
mentioning
confidence: 99%
“…These lessons comprise critical time school counselors spend in direct service to students. ASCA (2012) recommends school counselors spend 15%-45% of their time (depending on school level) delivering classroom guidance; thus, development of classroom guidance curriculum warrants careful consideration and intentionality (Lopez & Mason, 2018;Vernon, 2010).…”
mentioning
confidence: 99%
See 2 more Smart Citations